Production of biodiesel from high acid value waste cooking oil using an optimized lipase enzyme/acid-catalyzed hybrid process - Saifuddin N.; Raziah A.Z.; Farah H.N. (Hindawi Limited, 2023)
The present study is aimed at developing an enzymatic/acidcatalyzed hybrid process for biodiesel production using waste cooking oil with high acid value (poor quality) as feedstock. Tuned enzyme was prepared using a rapid drying technique of microwave dehydration (time required around 15 minutes). Further enhancement was achieved by three phase partitioning (TPP) method. The results on the lipase enzyme which was subjected to pH tuning and TPP, indicated remarkable increase in the initial rate of transesterification by 3.8 times. Microwave irradiation was found to increase the initial reaction rates by further 1.6 times, hence giving a combined increase in activity of about 5.4 times. The optimized enzyme was used for hydrolysis and 88% of the oil taken initially was hydrolyzed by the lipase. The hydrolysate was further used in acidcatalyzed esterification for biodiesel production. By using a feedstock to methanol molar ratio of 1:15 and a sulphuric acid concentration of 2.5%, a biodiesel conversion of 88% was obtained at 50 C for an hour reaction time. This hybrid process may open a way for biodiesel production using unrefined and used oil with high acid value as feedstock.